Band insulator to Mott insulator transition in 1T-TaS2 - Y. D. Wang (Nature Portfolio, 2020)
1T-TaS2 possesses complex electronic phase behaviors in transition-metal di-chalcogenides, undergoing several charge-ordered phases before finally into an insulating state of unknown origin. Here, the authors determine its electronic and structural properties experimentally, revealing its origin.